Systematically designating conservation areas for protecting habitat quality and multiple ecosystem services. (April 2017) - Lin, Yu-Pin; Lin, Wei-Chih; Wang, Yung-Chieh; Lien, Wan-Yu; Huang, Tao; Hsu, Chih-Chen; Schmeller, Dirk S.; Crossman, Neville D.
Abstract: Habitat quality and ecosystem supply are important factors when identifying conservation areas. Traditionally, conservation planning approaches focus solely on habitat. In this study we calculated habitat quality and five other ecosystem service values through the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) and also identified hotspots for each ecosystem service value through the Local Indicator of Spatial Association (LISA). Conservation areas that protect habitat quality and ecosystem services were simulated using the Zonation software with three scenarios of ecosystem service distribution. Four Boundary Length Penalties were also tested in terms of how well they produce suitable reserve sites. Finally, we developed the LISA-Zonation program which performs systematic conservation planning based on InVEST outputs. The ecosystem services hotspots represent spatial autocorrelations among neighboring cells and ecosystem service values, yielding conservation strategies which balance ecosystem service values with spatial connectivity. Our novel approach finds spatial autocorrelation of ecosystem services to identify conservation areas that provide potential benefits to people. Highlights: We use the InVEST model to calculate habitat quality and five ecosystem services values. We consider spatial autocorrelation and identify hotspots of ecosystem services. We simulate reserve areas that protect ecosystem services by the Zonation software. We developed the LISA-Zonation program for designating reserve areas.